Projeções do lobisomem na literatura: uma arqueogenealogia do corpo-espaço lupino - Santos, Jamille da Silva (2019)
This paper aims to verify the construction of the werewolf subject/character in the literature, its transformations and social relations, considering an archaeogenealogical theoretical-methodological proposal from the studies of Michel Foucault. Thinking the werewolf as a myth that has been transposed to time and space, based especially on the notes of Paul Zumthor, Suzi Frankl Sperber, André Jolles, Maria Auxiliadora Fontana, Luiz da Câmara Cascudo, we outline literary narratives as corpus, and as complementary corpus cinematographic works, historical documents, journalistic texts, song lyrics, that is, a variety of genres that we believe to be of fundamental relevance for understanding how the werewolf figure positions itself aesthetically over time. In a general way, we will investigate the recurrence of the position occupied by the werewolf subject/character, trying to evidence changes occurred around its aesthetic and social image. More specifically, first, we conducted a historical, literary, and cinematic survey of the werewolf myth over time. Then, we analyze the position of the subject/character, taking for this study the specific werewolf literature, focusing especially the body-space of this monster. Then we look at the punitive processes by which the lupine body was inserted into the Inquisition and how lycanthropy was no longer a crime, but a mental illness; we also reflected on how religion took over the lupine myth for its control procedures, especially those related to baptism. And finally, based on the literature, especially the brazilian one, we analyze how the werewolf myth was brought to the present, what changes occurred in its body-space and in its reading public; and finally we demonstrate an increase in youth literature productions with women metamorphosing into wolves.